Construction of Ni(CN)₂ /NiSe₂ heterostructures by stepwise topochemical pathways for efficient electrocatalytic oxygen evolution - Nai, Jianwei (2022)
Exploiting effective electrocatalysts based on elaborate heterostructures for the oxygen evolution reaction (OER) has been considered as a promising strategy for boosting water splitting efficiency to produce the clean energy-hydrogen. However, constructing catalytically active heterostructures with novel composition and architecture remains poorly developed due to the synthetic challenge. In this work, it is demonstrated that unique Ni(CN)2 /NiSe2 heterostructures, composed of single-crystalline Ni(CN)2 nanoplates surrounded by crystallographically aligned NiSe2 nanosatellites, can be created from nickel-based Hofmann-type coordination polymers through stepwise topochemical pathways. When employed as the OER electrocatalyst, the Ni(CN)2 /NiSe2 heterostructures show enhanced performance, which could be attributed to optimized geometric and electronic structures of the catalytic sites endowed by the synergy between the two components. This work demonstrates a rational synthetic route for creating a novel Ni-based OER electrocatalyst that possesses nanoscale heterostructure, whose composition, spatial organization, and interface configuration can be finely manipulated.